Results of the Application of the Original Method of Surgical Treatment of Patients with Severe Hallux Valgus - V. V. Epishin; S. M. Goodi; V. V. Kuznetsov; S. B. Korochkin; S. V. Filatova; I. A. Pakhomov (Acta Biomedica Scientifica, 2019)
Background. Traditional methods of surgical treatment of severe Hallux valgus (HV) lead to a large number of complications and poor results. In order to avoid complications and improve the quality of treatment, an original technique of double osteotomy of the first metatarsal bone has been proposed.The aim of the study was to conduct a comparative assessment of the results of applying the original technique in the treatment of patients with severe Hallux valgus.Materials and methods. A retrospective analysis of the treatment of 95 patients operated on at the Seversk Clinical Hospital for severe Hallux valgus in the period from 2008 to 2016 was performed. The study group included 60 patients who underwent surgery according to the original method. In a comparison group of 35 people, Logroshino's surgery was performed. Clinical, radiological, surgical and statistical research methods were used.Results. The final assessment of the results 1 year after the operation showed an unacceptably high number of Hallux valgus relapses, complications, and unsatisfactory results in the comparison group. The use of original approachesfor osteotomy of the first metatarsal bone in patients of the study group allowed to significantly improve treatment results and achieve good results in 85 % of cases.Conclusion. The proposed surgical technique is effective and shows statistically significantly better results 1 year after surgery. Application of the original technique will improve the results of surgical correction of the severe degree of Hallux valgus, which consists in reducing the number of complications and improving functional indicators.